The Dental Caries and Some Salivary Constituents among a Group of Ten Years Iraqi Passive Smokers - Hussein, Ali S; Al-Waheb, Athraa M (Journal of Baghdad College of Dentistry, 2016)
Background: Passive smoking and dental caries affect the integrity of the health of individuals and both of them affected by sociodemographic characteristics of those individuals. This research aimed to investigate the severity of dental caries in relation to salivary magnesium and zinc of stimulated whole saliva of a group of 10 years passive smokers in comparison with normal subjects. Materials and methods: the study group included 40 subjects (20boys and 20 girls), with an age of 10 years of passive smokers determined by a questionnaire. The control group included 40 normal subjects of the same gender and age of the study group. The diagnosis and recording of dental caries was measured by (D1-4MFS & d1-4mfs) index according to the criteria of Muhleman (1976). The collection of stimulated whole saliva was performed under standardized condition. The salivary samples were chemically analyzed for measuring of Zn and Mg. Results: The caries experience among study group was lower than that of control group for primary dentition but without significant difference while for permanent dentition it was equal. Salivary magnesium ions concentration was lower among study group compared with control group with high significant difference. Concerning salivary zinc ion concentration it was higher among study group with high significant difference among females and significant among males. Among males of study group, magnesium correlated negatively significantly with D1, the same correlation was recorded among females where it was with D1and D2 while it was correlated positively highly significantly with d1 of control group and significantly with d1 and D3 among males of control group. For salivary zinc it was correlated negatively highly significantly with D3 of study group. Conclusion: Passive smoking has no effects on dental caries rather than it affects certain salivary constituents.